Archibald Roosevelt papers - Roosevelt, Archibald, 1918-1990.
Correspondence, diaries, intelligence reports, notes, academic notebooks, scrapbooks, printed matter, maps, photographs, and other papers pertaining primarily to Roosevelt's service as a U.S. Army intelligence officer stationed in Algeria, Iran, Iraq, Morocco, and Tunisia during and immediately after World War II. Includes his observations on Arab nationalism and politics, Arab discontent with French colonial administration in North Africa, Soviet influence in the Iranian province of Azerbaijan, the short-lived Kurdish republic in northern Iran, Kurds and other tribes of Iraq, and the partition of Palestine. Also includes miscellaneous personal papers and photographs from his career and of the Roosevelt family.
Part II of the collection relates to Roosevelt's work from 1974 to 1990 as director of international relations for Chase Manhattan Bank and includes correspondence and reports relating to political, social, and economic developments in the Middle East and Africa. Also includes correspondence and reviews of his published memoirs, For Lust of Knowing : Memoirs of an Intelligence Officer (1988) as well as personal correspondence, diaries, engagement calendars, financial records, military papers, photographs, and printed matter. Includes material pertaining to the personal and social activities of Roosevelt and his wife Selwa Roosevelt.
Intelligence officer, diplomat, and consultant. Full name: Archibald Bulloch Roosevelt Jr.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Roosevelt, Selwa; Roosevelt family; Chase Manhattan Bank; United States. -- Army -- Foreign service -- Iran; United States. -- Army -- Intelligence specialists; United States. -- Central Intelligence Agency; Banks and banking, International; Intelligence service -- United States; Kurds -- Iran; Kurds -- Iraq; Nationalism -- Arab countries; Tribes -- Iraq; World War, 1939-1945 -- Algeria; World War, 1939-1945 -- Iraq; World War, 1939-1945 -- Morocco; World War, 1939-1945 -- Tunisia; World War, 1939-1945 -- Military intelligence -- United States; Africa -- Economic conditions; Africa -- Politics and government; Africa -- Social conditions; Africa, North -- Foreign relations -- United States; Africa, North -- History -- 1882-; Algeria -- Foreign relations -- United States; Arab countries -- Economic conditions; Arab countries -- Foreign relations -- United States; Arab countries -- Politics and government; Arab countries -- Social conditions; Azerbaijan -- Relations -- Soviet Union; France -- Colonies -- Africa; Iran -- Foreign relations -- United States; Iraq -- Foreign relations -- United States; Middle East -- Foreign relations -- United States; Morocco -- Foreign relations -- United States; Palestine -- History -- Partition, 1947.; Soviet Union -- Relations -- Azerbaijan; Tunisia -- Foreign relations -- United States; United States -- Foreign relations -- Africa, North; United States -- Foreign relations -- Algeria; United States -- Foreign relations -- Iran; United States -- Foreign relations -- Iraq; United States -- Foreign relations -- Middle East; United States -- Foreign relations -- Morocco; United States -- Foreign relations -- Tunisia; United States -- Foreign relations -- 20th century; Army officers; Bankers; Intelligence officers